2012
DOI: 10.1242/jeb.069625
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic compass orientation in two strictly subterranean rodents: learned or species-specific innate directional preference?

Abstract: SUMMARYEvidence for magnetoreception in mammals remains limited. Magnetic compass orientation or magnetic alignment has been conclusively demonstrated in only a handful of mammalian species. The functional properties and underlying mechanisms have been most thoroughly characterized in Ansellʼs mole-rat, Fukomys anselli, which is the species of choice due to its spontaneous drive to construct nests in the southeastern sector of a circular arena using the magnetic field azimuth as the primary orientation cue. Be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 49 publications
1
36
0
Order By: Relevance
“…Magnetic orientation has been convincingly demonstrated in six rodent species using nesting in a circular arena or a radial maze as an orientation assay (Burda et al, 1990(Burda et al, , 1991Marhold et al, 1997aMarhold et al, ,b, 2000Kimchi and Terkel 2001;Deutschlander et al, 2003;Muheim et al, 2006;Oliveriusová et al, under review). The very fact that this assay is not based on any goal directed behavioral task raises the question as to whether the spontaneous drive to build nests in a certain sector of the arena/maze constitutes true compass orientation or MA.…”
Section: Rodent Nesting In a Circular Arena: True Compass Or Magneticmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic orientation has been convincingly demonstrated in six rodent species using nesting in a circular arena or a radial maze as an orientation assay (Burda et al, 1990(Burda et al, , 1991Marhold et al, 1997aMarhold et al, ,b, 2000Kimchi and Terkel 2001;Deutschlander et al, 2003;Muheim et al, 2006;Oliveriusová et al, under review). The very fact that this assay is not based on any goal directed behavioral task raises the question as to whether the spontaneous drive to build nests in a certain sector of the arena/maze constitutes true compass orientation or MA.…”
Section: Rodent Nesting In a Circular Arena: True Compass Or Magneticmentioning
confidence: 99%
“…The situation is less clear in strictly subterranean, congenitally microphthalmic mole-rats, which exhibit a spontaneous directional preference (Burda et al, 1990(Burda et al, , 1991Marhold et al, 1997aMarhold et al, ,b, 2000Kimchi and Terkel 2001;Oliveriusová et al, under review). Indeed, it has been repeatedly suggested that the magnetic orientation of mole-rats can be viewed as an expression of MA (Deutschlander et al, 2003;Muheim et al, 2006;Phillips et al, 2010).…”
Section: Rodent Nesting In a Circular Arena: True Compass Or Magneticmentioning
confidence: 99%
“…Among mammals, bats [3,4], two families of subterranean molerats [57], as well as Siberian hamsters and C57BL/6 mice [810], have been shown to rely on magnetic cues to determine compass headings. Magnetic cues have also been implicated in the tendency of free-living mammals as diverse as cattle, deer, and foxes to preferentially align their body axes along the North–South axis [1113].…”
Section: Introductionmentioning
confidence: 99%
“…It is noteworthy that all of the studies demonstrating the use of magnetic cues by rodents, with the exception of [14], have used assays that involve spontaneous or learned nest positioning behaviors [6,7,9,15]. Consequently, one possible explanation for the lack of evidence in other hamster and mouse studies is that rodents only utilize magnetic compass cues in certain behavioral contexts such as nest-building.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation